Syringomyelia in pregnancy - is caesarean section the best option for delivery - a case report - Bilal, Hakim Gharib; Ramli, Roszaman; Abd. Wahab, Noraziana; Che Yaakob, Che Anuar; Abdullah, Jefri (Faculty of Medicine, International Islamic University Malaysia, 2009)
Syringomyelia is a rare neurological disease, which is characterized by the formation of a cyst in the spinal cord. The aetiology of the disease still remains controversial. The damage to the spinal cord results in headache, weakness, stiffness and numbness on both lower and upper limbs. Only few a cases of syringomyelia in pregnancy have been reported thus far. As such, there is no standard management of intrapartum care. We present a case of symptomatic syringomyelia in pregnancy, its management and literature review. The mode of delivery with risks for vaginal route is discussed.